P06 Delivery of a school health and nutrition programme for kenyan children: a feasibility study. (27th April 2015) - Eder, B; Bogie, J; Magnus, D
Abstract : Aims: Health is a key factor in enabling universal access to education. Children miss over 200 million days of school every year due to illness. Traditionally, vertical approaches have been used to individually tackle child health and nutrition problems such as malnutrition or malaria. However, these interventions overlook the complex interactions between them. We therefore sought to develop a comprehensive, integrated school health and nutrition programme to produce long-term and sustainable improvements to child health and education outcomes. Methods: A 3 year pilot study was carried out in a population of 2, 000 children aged 5–16 in rural Western Kenya. The programme comprised school meals, vitamin A supplementation, insecticide-treated bed nets, deworming, hand washing and health education. Data were collected on programme delivery and on health, nutrition and education parameters. Results: 2103 children were dewormed using Albendazole, supplied with insecticide-treated bed nets and Vitamin A was given to all children under 5. School meals were provided daily to all children. Additional water points with soap were installed with a 32.5% observational increase in clean hands and 86% increased soap use. Preliminary results show increased school enrolment and reductions in school absenteeism (OR 0.70, 95% CI 0.61–0.82, p= < 0.001), in anaemia (OR 0.25, 95% CI 0.16–0.40, p= < 0.001) and undernutrition, both stunting (OR 0.56, 95% CI 0.48–0.65, p= < 0.001) and underweight (OR 0.55, 95% CI 0.42–0.73, p = 0.001). Conclusion: Our experience shows that a comprehensive school health and nutrition programme is feasible and that monitoring for health and education outcomes is possible in this context. The data suggest improvements in childhood anaemia and nutrition in conjunction with improved school attendance and enrolment. Complex interventions for improving school health are feasible and can produce long-term benefits above and beyond vertical programme initiatives.